Penggunaan Aplikasi Youtube Untuk Meningkatkan Kemampuan Mengenal Huruf Hijaiyah Pada Anak Usia 4-5 Tahun - Jubaedah, Endah; Nurazizah, Hanifah (LP2M STAI Al-Musaddadiyah Garut, 2025)
This research was motivated by observational data which showed the low level of achievement in recognizing hijaiyah letters for early childhood at the Hikmatul Huda IT Kindergarten with the discovery of several problems including; the ability to recognize hijaiyah letters in group A is still lacking, children recognize hijaiyah letters through the medium of iqro books, but the ability to recognize letters through their letter shapes is still lacking, children are not yet able to name and differentiate hijaiyah letters randomly, children cannot pronounce the letters hijaiyah beginning to end both in singing or memorizing and how to pronounce the letters correctly. thus making children's recognition of hijaiyah letters less stimulating. The aim of this research is to describe the use of the YouTube application to recognize hijaiyah letters in children aged 4-5 years at the IT Hikmatul Huda Kindergarten. The subjects in this study were 17 respondents with 8 male subjects and 9 female subjects. The type of research used in this research is qualitative research with a classroom action research or PTK design. The results of this research show that the use of the YouTube application to recognize hijaiyah letters in children aged 4-5 years at the IT Hikmatul Huda Kindergarten shows a significant increase, this can be seen from the percentage of success, from the results of initial observations there are 0% of children developing very well , 18% of children are developing according to expectations, 29% of children are starting to develop and 53% of children are not yet developing. After implementing the use of the YouTube application to improve the ability to recognize hijaiyah letters in children aged 4-5 years, the final results of cycle I reached a 53% increase in the ability to recognize hijaiyah letters in children aged 4-5 years, and the final results of cycle II reached 100% . Keywords: Early Childhood; YouTube App; Hijaiyah letters